Policy to Combat Illegal Narcotics Trafficking in Indonesia - Kaisar Julio; Afdhal Afdhal (Pelopor Publikasi Akademika, 2026)
The illicit trafficking of narcotics in Indonesia is a serious problem that is complex, organized, and transnational in nature, requiring a comprehensive and sustainable countermeasures policy. This research aims to analyze the policy for combating illicit drug trafficking in Indonesia, including the effectiveness of its implementation and the obstacles faced by law enforcement officials. The research method employed is a normative juridical approach utilizing statutory and conceptual approaches, supported by secondary data in the form of primary, secondary, and tertiary legal materials. The results indicate that the policy for combating illicit drug trafficking in Indonesia is still dominated by a repressive approach through firm law enforcement, as stipulated in Law Number 35 of 2009 concerning Narcotics. However, the implementation of this policy has not been fully optimal due to various obstacles, including limited human resources, weak inter-agency coordination, and technological developments exploited by drug trafficking networks. Furthermore, preventive and rehabilitative approaches have not been implemented optimally, and have thus far failed to significantly reduce drug abuse rates. Therefore, strengthening policies that integrate penal and non-penal approaches, enhancing synergy between institutions, and optimizing the role of the community in prevention efforts are necessary. It is expected that these measures will render the policy for combating illicit drug trafficking in Indonesia more effective in protecting the public and maintaining national resilience.